Tourismusentwicklung im Rentenstaat. Am Beispiel von Petra, dem Brennpunkt des Jordanischen Tourismus - Barham, Nasim; Kopp, Horst (ERDKUNDE, 2001)
The paradigm of the rentier state implicates the so-called rent-seeking mentality of entrepreneurs besides macro-economic, political and social factors. Nevertheless empirical studies of this phenomenon have been the exception up to now. The question remains especially whether even modern sectors of the economy in a rentier state follow the theoretical paradigm or not. - This study on the tourism sector of Jordan, especially on recent developments in Petra, concentrates on the behaviour and the strategies of action of investors. Although the conditions of the tourism sector have become much better since the peace treaty between Jordan and Israel, the study shows that some general aspects of the rent-seeking mentality continue to exist for the time being. So the sector will remain prone to crises instead of being dynamic.